Narrativas da floresta nacional de Tefé: expressões de saber do aluno ribeirinho e a sua transposição didática para o Ensino de Ciências Naturais - Zurra, Raiziana Mary de Oliveira (2011)
This research is a reflection about the implicit types of knowledge in the narratives of Tefé National Forest (FLONA) population and its practical application in the teaching and learning process of Natural Sciences. The present research intended to learn how you can translate the scientific knowledge about traditional knowledge found in these popular narratives within the multisseriate classrooms composed by elementary school students for the purpose of optimizing the process of teaching and learning of Natural Sciences. The present research consists in highlighting the mythical and legendary narratives as a cognitive enhancer, arousing curiosity and fostering new opportunities of understanding conceptual contents, procedures and attitudes, once learning requires a significant set of complex cognitive processes. This work presents a qualitative and quantitative studys under a structuralist approach, based on the principles of Anthropology, Biology, Literature, Psychology and Pedagogy. In order to perform the proposed analysis, we searched for authors who would theoretically support our subject: the theoretical and methodological knowledge by Edgard Morin and Cecilia Minayo, Mircea Eliade, Vladimir I. Propp, Marcos Frederico Krüger, Terry Eagleton, Therezinha de J.P. Fraxe, Maria Zaira Turchi, Boaventura de Souza Santos, Carlos Antonio Mascia Gottschall, Chevallard, David Ausubel e L. S. Vigotski. At the end of the present study it was possible to propose as a product, a methodology strategy whose narratives are used to elicit students' previous experiences, and thus mediate the chain of didactic transposition about Natural Sciences contents. This feature is indicated, preferably where the multigrade schools are still a reality, in order to facilitate both the redefinitions of specific science content, and further prospects of development of an interdisciplinary classroom. The obtained results by the mentioned survey indicate that few studies focus on the relationship between popular literature and Science teaching, and the local folklore narratives, especially myths, legends and tales, provide new possibilities to overcome two serious Illiteracies: the scientific and the literary ones. It is expected that this research can possibly contribute to student‟s teaching and learning process and that others realize the importance of acquiring other knowledges for science education development in schools where this research was conducted.